TEACHING ENGLISH AS A FOREIGN LANGUAGE: MAKING USE OF SPONTANEOUS LANGUAGE - Eshmirzayeva Nozima Bahodir qizi; Atoboyeva Aziza Muhiddin qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: Current article is devoted to the problems of teaching methods of English as a foreign languages. In this article we look through different methods in this field. Methods of foreign language teaching and its relation to other sciences. Methods of foreign language teaching is understood here as a body of scientifically tested theory concerning the teaching of foreign languages in school and other educational institutions. Teaching a foreign language means first and foremost the formation and development of students’ habits and skills in listening, speaking, writing, and reading.